2003
DOI: 10.1093/hmg/ddg001
|View full text |Cite
|
Sign up to set email alerts
|

Connexin30 (Gjb6)-deficiency causes severe hearing impairment and lack of endocochlear potential

Abstract: The gap junction protein connexin30 (Cx30) is expressed in a variety of tissues that include epithelial and mesenchymal structures of the inner ear. We generated Cx30 (Gjb6) deficient mice by deletion of the Cx30 coding region. Homozygous mutants (Cx30((-/-))) were born at the expected Mendelian frequency, developed normally and were fertile. However, they exhibit a severe constitutive hearing impairment. From the age of hearing onset, these mice lack the electrical potential difference between the endolymphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
212
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(223 citation statements)
references
References 39 publications
9
212
2
Order By: Relevance
“…Mutations in the Cx26 and Cx30 genes are a common cause of autosomal recessive non-syndromic deafness in humans (Nickel and Forge 2008). In mouse models, the deletion of Cx26 or Cx30 from epithelial cells results in hair cell death (CohenSalmon et al 2002;Teubner et al 2003). Our dye transfer experiments here showed that the gap junctions between root cells were permeable to Lucifer yellow, a large and negatively charged dye molecule.…”
Section: Root Cells Form the Lateral Limits Of The Epithelial Gap Junmentioning
confidence: 48%
“…Mutations in the Cx26 and Cx30 genes are a common cause of autosomal recessive non-syndromic deafness in humans (Nickel and Forge 2008). In mouse models, the deletion of Cx26 or Cx30 from epithelial cells results in hair cell death (CohenSalmon et al 2002;Teubner et al 2003). Our dye transfer experiments here showed that the gap junctions between root cells were permeable to Lucifer yellow, a large and negatively charged dye molecule.…”
Section: Root Cells Form the Lateral Limits Of The Epithelial Gap Junmentioning
confidence: 48%
“…Digenic inheritance in those cases is supported by the findings that both genes, GJB2 and GJB6, encode for gap junction proteins, connexin 26 and connexin 30, respectively, and are expressed in the same cells in the rat cochlea and in the cochlea of the 22-week-old human embryo (Lautermann et al, 1999). Likewise, mice mutants that are homozygous for a deletion of the GJB6 coding region develop NSHL (Teubner et al, 2003) representing a mouse model for this type of HL.…”
Section: Discussionmentioning
confidence: 95%
“…The location of these proteins along the membranes of the different cells of the adult stria vascularis is depicted in Figure 1(B). Disrupting the function of any of these proteins (including connexin proteins) in the stria vascularis or at other locations in the cochlea where they are thought to be involved in K + homeostasis results in immediate SNHL (Cohen‐Salmon et al, 2002; Teubner et al, 2003; Nin et al, 2008). In many cases of both syndromic (as mentioned above) and nonsyndromic SNHL, the endocochlear potential is likely to be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Although less frequent, mutations in GJB6 ( CX30 ) (Grifa et al, 1999; del Castillo et al, 2002) and GJA1 (CX43) (Liu et al, 2001; Hong et al, 2010) have also been linked to SNHL. These gap junction proteins are thought to play a role in maintaining cochlear ion homeostasis and the endocochlear potential, as shown in Gjb6 ‐deficient mice (Teubner et al, 2003), by passively recycling K + ions back to the stria vascularis. The observed expression in the developing human cochlea is in support of this model.…”
Section: Discussionmentioning
confidence: 99%